Design of a didactic resource for the psychopedagogical intervention of students with written language disorders (dyslexia-dysgraphia): a systematic review (Orkopata. Revista de Lingüística, Literatura y Arte, 2025)
The present article analyzes the characteristics and alterations in students with dyslexia and dysgraphia as a neuropsychological disorder that affects written language and its impact on cognitive, academic, and socio-emotional areas. Its objective is to design a didactic resource aimed at teachers for the psychopedagogical intervention of schoolchildren with dyslexia and dysgraphia, considering that these disorders significantly affect students' quality of life. It proposes a qualitative approach methodology through a systematic review based on PRISMA criteria. The search included databases such as Scopus, SciELO, Google Scholar, Dialnet, and Redalyc, considering original studies on dyslexia and dysgraphia published between 2014 and 2024 in Spanish or English. Keywords such as “dyslexia and dysgraphia,” “intervention,” and “didactic resource” were used. The review confirms the need to train and guide teachers in effective intervention strategies. It describes the characteristics and needs of students with dyslexia and dysgraphia. The study highlights the etiology, classification, and prevalence of these disorders and their impact on students' quality of life. Based on these needs, the proposed didactic resource, "Tejiendo Palabras," represents a significant innovation in supporting students with these disorders. Its multisensory approach, the incorporation of technology, and the prominence of the neuropsychological and psycholinguistic approach ensure a comprehensive and effective educational intervention, fostering a more inclusive and equitable learning environment adapted to the specific psycho-affective needs of each student.
Keywords: dyslexia; dysgraphia; didactic resource; multisensory strategies; psychopedagogy